Comparative and Stylometric Analysis of the Crónica del Perú and the Comentarios reales de los incas Using Text Analysis and Georeferencing tools - Gonzales Cam, Celso (2024)
The present study consists of the textual analysis of the Chronicles of Peru, written by Pedro Cieza de León, between the years of 1540 to 1550 and The Royal Commentaries of the Incas, by Inca Garcilaso de la Vega published in 1609. This comparative analysis deals with to explore the differences between both chroniclers, who each have a different perspective as historical witnesses of their time. Two exploratory tools have been used, such as Voyant Tools and the georeferencing with Recogito, to carry out a font exploration and its geographical scope of its texts.